Bioorthogonally Functionalized NAD+ Analogues for In‐Cell Visualization of Poly(ADP‐Ribose) Formation. Issue 27 (15th April 2016) - Wallrodt, Sarah; Buntz, Annette; Wang, Yan; Zumbusch, Andreas; Marx, Andreas
Abstract: Poly(ADP‐ribos)ylation (PARylation) is a major posttranslational modification and signaling event in most eukaryotes. Fundamental processes like DNA repair and transcription are coordinated by this transient polymer and its binding to proteins. ADP‐ribosyltransferases (ARTs) build complex ADP‐ribose chains from NAD + onto various acceptor proteins. Molecular studies of PARylation thus remain challenging. Herein, we present the development of bioorthogonally functionalized NAD + analogues for the imaging of PARylation in vitro and in cells. Our results show that 2‐modified NAD + analogues perform remarkably well and can be applied to the in‐cell visualization of PARylation simultaneously in two colors. This tool gives insight into the substrate scope of ARTs and will help to further elucidate the biological role of PARylation by offering fast optical, multichannel read‐outs. Abstract : Now you see it : NAD + is metabolized and built into poly(ADP‐ribose) by ADP‐ribosyltransferases, and this PARylation affects various biological processes. Methods for the intracellular visualization of this process are rare and limited. To overcome this, new NAD + analogues functionalized with bioorthogonal reporter groups were developed and successfully applied to the selective two‐color labeling of poly(ADP‐ribose) formation in cells.